2021
DOI: 10.1039/d1ra01372f
|View full text |Cite
|
Sign up to set email alerts
|

A label-free electrochemical biosensor based on 3D cubic Eu3+/Cu2O nanostructures with clover-like faces for the determination of anticancer drug cytarabine

Abstract: Electrochemical biosensor based on three-dimensional (3D) cubic of Eu3+/Cu2O with clover-like face nano-structures and ds-DNA modified carbon paste electrode for detecting cytarabine was fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Two sensing protocols for indirect determination of methotrexate (folic acid analogs) were proposed and are based on dsDNA modified GCE [143] and DNA-based GCE modified with GO. [144] The results revealed that the sensor proposed by Chen et al [144] showed improved analytical parameters (LOD of 7.6 nM; good recovery in pharmaceutical formulation and spiked urine samples; selectivity study) when compared to sensor developed by Rafique et al [143] Indirect determination of three antimetabolites, namely 6-mercaptopurine (purine analog), [145] 5-fluorouracil, [146] and cytarabine [147] (both pyrimidine analogs), was performed on DNA sensors based on PGE modified with p-Py, 4-dodecylbenzenesulfonic acid, and functionalized MWCNTs, [145] GCE modified with poly-bromocresol purple (p-BCP), [146] and CPE modified with europium(III)-doped copper(I) oxide NPs ((Eu 3þ -Cu 2 O)NPs), [147] respectively. Moreover, two electroanalytical systems for indirect gemcitabine (pyrimidine analog) detection were developed, also using dsDNA sensors based on GCE modified with poly-(2,6-pyridinedicarboxylic acid) [148] and CPE modified with AgNPs, MWCNTs, and MIP.…”
Section: Aunpsmentioning
confidence: 95%
See 1 more Smart Citation
“…Two sensing protocols for indirect determination of methotrexate (folic acid analogs) were proposed and are based on dsDNA modified GCE [143] and DNA-based GCE modified with GO. [144] The results revealed that the sensor proposed by Chen et al [144] showed improved analytical parameters (LOD of 7.6 nM; good recovery in pharmaceutical formulation and spiked urine samples; selectivity study) when compared to sensor developed by Rafique et al [143] Indirect determination of three antimetabolites, namely 6-mercaptopurine (purine analog), [145] 5-fluorouracil, [146] and cytarabine [147] (both pyrimidine analogs), was performed on DNA sensors based on PGE modified with p-Py, 4-dodecylbenzenesulfonic acid, and functionalized MWCNTs, [145] GCE modified with poly-bromocresol purple (p-BCP), [146] and CPE modified with europium(III)-doped copper(I) oxide NPs ((Eu 3þ -Cu 2 O)NPs), [147] respectively. Moreover, two electroanalytical systems for indirect gemcitabine (pyrimidine analog) detection were developed, also using dsDNA sensors based on GCE modified with poly-(2,6-pyridinedicarboxylic acid) [148] and CPE modified with AgNPs, MWCNTs, and MIP.…”
Section: Aunpsmentioning
confidence: 95%
“…Moreover, the elucidation of the interaction mechanism of dsDNA with cytarabine was made using CPE modified with dsDNA and (Eu 3þ -Cu 2 O)NPs by DPV. [147] Results showed condensation of the DNA double helix being a consequence of a complex formation. Authors pointed out that the binding mode of cytarabine to dsDNA cannot occur via intercalative binding or electrostatic interaction.…”
Section: Aunpsmentioning
confidence: 99%
“…Photoactive nanomaterials generate electron-hole pairs material when interacting with light radiation. The charge transfer process in these materials can be improved by modifying working electrodes with nanostructure materials such as titanium dioxide (TiO 2 ), 30,31 bismuth sulde (Bi 2 S 3 ), 32,33 zinc oxide (ZnO), 34 tungsten trioxide (WO 3 ), 35 cerium dioxide (CeO 2 ), 36 La 2 O 3 @Cu 2 S, 37 cupric oxide (CuO), 38,39 cuprous oxide (Cu 2 O), 40 and graphitic carbon nitride (g-C 3 N 4 ). 38,39 Among these, copper(II) oxide (CuO) is one of the promising materials of considerable interest, as it is a p-type semiconductor material with a monoclinic crystal structure and has a narrow energy band gap of 1.2-1.7 eV for higher visible and infrared light absorption.…”
Section: Introductionmentioning
confidence: 99%